2017
DOI: 10.5505/itujfa.2017.16878
|View full text |Cite
|
Sign up to set email alerts
|

Development of urban hierarchies at the country and regional levels in Turkey

Abstract: The purpose of this paper is to illustrate the hierarchical distribution of different city size groups at the country and regional level between 1945 and 2015 in Turkey. During this period, previous studies have illustrated that human mobility played an important role for the physical and socio-economic transformation of cities and regions. At the country level, first, while the growth rate of the number of smaller cities was higher than the others, the growth rate of population was the highest in the large ci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…In this distribution, it has been found that the physical and economic development levels of Cluster 1, Cluster 7 and Cluster 9 cities where fractal values are measured above the average are generally better. Socio-economic findings in the article "Development of urban hierarchies at the country and regional levels in Turkey" published by Kaya and Dökmeci (2017) also support this hypothesis. • The exception of a mega-city like Izmir with its low fractal dimension and high lacunarity coefficient is due to the sprawl of the urban pattern.…”
Section: Discussionmentioning
confidence: 70%
“…In this distribution, it has been found that the physical and economic development levels of Cluster 1, Cluster 7 and Cluster 9 cities where fractal values are measured above the average are generally better. Socio-economic findings in the article "Development of urban hierarchies at the country and regional levels in Turkey" published by Kaya and Dökmeci (2017) also support this hypothesis. • The exception of a mega-city like Izmir with its low fractal dimension and high lacunarity coefficient is due to the sprawl of the urban pattern.…”
Section: Discussionmentioning
confidence: 70%
“…In their comprehensive study on the distribution of cities in Turkey, Deliktaş et al (2013) found that the location of a city has a positive impact on migration and agglomeration of services as well as specialization in manufacturing industry. Kaya and Dökmeci (2017) showed that due to economic constraints and higher emigration rates, the hierarchical distribution of cities differentiates in the Eastern and Western parts of Turkey.…”
Section: Introductionmentioning
confidence: 99%